2019
DOI: 10.3390/nano9101447
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Semiconductor Morphology on Photocatalytic Activity of Plasmonic Photocatalysts: Titanate Nanowires and Octahedral Anatase Nanoparticles

Abstract: Octahedral anatase particles (OAP) with eight exposed and thermodynamically most stable (101) facets were prepared by an ultrasonication-hydrothermal (US-HT) reaction from potassium titanate nanowires (TNW). The precursor (TNW) and the product (OAP) of US-HT reaction were modified with nanoparticles of noble metals (Au, Ag or Pt) by photodeposition. Samples were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), diffuse reflectance spectroscopy (DRS), scanning transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…The synthesized materials have shown interesting textural and morphological properties which support their use as photocatalysts in different processes. [108][109][110][111] Most of the photo catalytic processes described for titanium dioxidebased sys tems are focused on environmental issues, however, there are several other options for these materials in energyrelated tech nologies, such as for example water splitting, [6] solar cell com ponents, [106] and/or dehalogenation of solid or liquid wastes. [71] The possibility of degrading pollutants from an energy source that is harmless to nature, such as visible light, opens up a wide range of possibilities for the materials prepared in this work.…”
Section: Applications Of the Materials In Catalytic And Photocatalytic Processesmentioning
confidence: 99%
“…The synthesized materials have shown interesting textural and morphological properties which support their use as photocatalysts in different processes. [108][109][110][111] Most of the photo catalytic processes described for titanium dioxidebased sys tems are focused on environmental issues, however, there are several other options for these materials in energyrelated tech nologies, such as for example water splitting, [6] solar cell com ponents, [106] and/or dehalogenation of solid or liquid wastes. [71] The possibility of degrading pollutants from an energy source that is harmless to nature, such as visible light, opens up a wide range of possibilities for the materials prepared in this work.…”
Section: Applications Of the Materials In Catalytic And Photocatalytic Processesmentioning
confidence: 99%
“…Accordingly, various methods and procedures of its modification have been proposed, including surface modification, [4][5][6] doping, 7-9 coupling [10][11][12] and morphology architecture. [13][14][15] For example, modification with noble metals (NMs) results in double action, i.e., an activity enhancement under UV (NM working as an electron scavenger) [16][17][18] and vis response due to plasmonic properties. [19][20][21][22][23] Accordingly, NM-modified semiconductors with activity under vis irradiation, known as plasmonic photocatalysts, have been of great interest recently.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison between 0D and 1D plasmonic photocatalysts have been performed by Wei et al for OAP (faceted anatase titania) and titanate nanowires (TNWs; precursor used for OAP synthesis) modified with NPs of Au, Ag, and Pt [116]. It has been confirmed that the modifications with noble metals have improved the photocatalytic performance of both semiconductors significantly under UV and vis irradiation.…”
Section: One-dimensional Plasmonic Photocatalystsmentioning
confidence: 98%